Detection of Molds Which Present in Domestic's Refrigerators in Baghdad City - Ahmed Sahi Dwaish (Journal of Global Pharma Technology, 2017)
Twenty species were isolated from 50 samples of domestic's refrigerators in Baghdad city , during September 2016 which were Aspergillus niger, Aspergillus. flavus, , Aspergillus. fumigatus, Aspergillus duricaulis , Aspergillus novofumigatus, Aspergillus heteromorphus Aspergillus aculeatus , Aspergillus nidulans , Curvularia lunata ,Penicillium sp., Fusarium oxysporum, , Alternaria alternate, Cladosporium sp. Trichoderma sp., Mucor, Rhizopus sp., Rhodotorula mucilaginosa, , Stachybotrys and yeast. Among the isolated species Aspergillus niger, was the most abundant (14.92%) followed by Aspergillus flavus (10.14%), while less abundant (0.95 & 0.63 %) Cladosporium sp. &., Mucor respectively.